2016
DOI: 10.1186/s13567-015-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-entry blockade of small ruminant lentiviruses by wild ruminants

Abstract: Small ruminant lentivirus (SRLV) infection causes losses in the small ruminant industry due to reduced animal production and increased replacement rates. Infection of wild ruminants in close contact with infected domestic animals has been proposed to play a role in SRLV epidemiology, but studies are limited and mostly involve hybrids between wild and domestic animals. In this study, SRLV seropositive red deer, roe deer and mouflon were detected through modified ELISA tests, but virus was not successfully ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 68 publications
6
84
0
Order By: Relevance
“…Compared to strain Ep-1PNA367, most of the nucleoli of strain Ep-1PNA367T1 were disintegrated with dispersed chromatin, and some mitochondria were destroyed or swelled (Fig 1C). More interestingly, some spherical virus-like particles (VLPs) with sizes of 65~70 nm in diameter were localized near the nuclear membrane area (Fig 1C), which is reminiscent of viral factory-like areas encapsulated with double membrane structure, as previously reported in virus-infected plants [50]. Similar structures were not observed in strain Ep-1PNA367.…”
Section: Resultssupporting
confidence: 79%
“…Compared to strain Ep-1PNA367, most of the nucleoli of strain Ep-1PNA367T1 were disintegrated with dispersed chromatin, and some mitochondria were destroyed or swelled (Fig 1C). More interestingly, some spherical virus-like particles (VLPs) with sizes of 65~70 nm in diameter were localized near the nuclear membrane area (Fig 1C), which is reminiscent of viral factory-like areas encapsulated with double membrane structure, as previously reported in virus-infected plants [50]. Similar structures were not observed in strain Ep-1PNA367.…”
Section: Resultssupporting
confidence: 79%
“…It was shown that the pathogen-specific immune defense reaction of the mammary epithelial cell (MEC) 9 determines the ability of the udder to fighting off bacteria 10, 11 . Using MEC it was found in vitro that challenges with E .…”
Section: Introductionmentioning
confidence: 99%
“…IHNv is the exception, as this virus is endemic to Sockeye salmon and Rainbow trout populations on the West coast of North America and can cause considerable losses of juvenile (fry-smolt) salmon in freshwater (Wolf, 1988); this virus has also spread to Europe and Asia (Dixon et al , 2016). The level of IHNv impact is highly species-specific.…”
Section: Discussionmentioning
confidence: 99%